Combined vascular malformation mimicking spitzoid neoplasm. - Viglizzo, G.; Herzum, A.; Gariazzo, L.; Buffelli, F.; Occella, C. (European Journal of Pediatric Dermatology, 2022)
Vascular malformations (VM) are congenital dysplastic disorders, sometimes quiescent until mechanical or hormonal stimuli make them more evident. When composed of one type of vessel (venous/lymphatic/arterial) the VM are called “simple”. Several vascular components can co-exist, forming a “combined” VM (CVM), as in the case presented (2). In the present case, the warty component clinically resembled verrucous circumscribed lymphangioma (1, 3), which may be a normal evolution of circumscribed lymphangioma; the concomitant presence of malformed veins was responsible for the dermoscopically visible blood vascular structures. However, the current case poses clinically important problems of differential diagnosis with other disorders, from common wart, to tuberculosis and spitzoid neoplasm (...).